PERENCANAAN PERAWATAN IMPELLER DAN SHAFT FRESH WATER PUMP DENGAN METODE PREDICTIVE MAINTENANCE - Ahmad Muzzammil; Nurvita Arumsari; Benedicta Dian Alfanda (Politeknik Perkapalan Negeri Surabaya, 2020)
A maritime transportation based company used corrective maintenance on these two component,impeller and shaft of fresh water pump inside their ship’s water cooling system. While using correctivemaintenance, these two components are getting maintained when its already in worse condition and made thesystem down. Therefore, a reliability analysis is performed using predictive method to predict when will these twocomponent would break down and then scheduled to fix based on MTTF value of component. Then, the systemwould run without getting disrupted because of the unit’s downtime.